Servitization to manage a changing market How the cable manufacturing industry could address the changes in the energy sector - Lindberg, Olivia; Felixson, Ellen (My University, 2023)
Electrification and the use of green fragmented energy sources are major trends in the energy sector, putting the energy grid under increased pressure where both maintenance and expansion of the infrastructure are needed. This, in turn, transfers the pressure upstream to the cable manufacturing industry to deliver the needed infrastructure and meet the changes in the market. One way of handling changes in a market, where the focus is on better meeting the needs of the customers is through servitization, which has been a trend for manufacturing firms wanting to create additional value. With this background, this study aimed to investigate how the cable manufacturing industry could address the changes in the energy sector by servitization. To do this, the study investigated where the cable manufacturing industry is positioned in the context of servitization and its implications to better understand the potential and possibilities of undergoing servitization. The study took the form of a case study, where the perspective of the cable manufacturing industry was taken to assess the potential and implications of servitized offerings towards the energy sector. The actors targeted in the energy sector were electricity network companies. This since they are responsible for the infrastructure of the electricity grid where ways of handling the increased pressure on the grid are needed. To understand the internal and external context of the cable manufacturing industry, two focus groups were held at the case study company, CSC, while five semi-structured interviews were conducted at the electricity network companies, ENCs. The study showed that the cable manufacturing industry is in the early phases of advanced services in a servitization journey and that there is a lot of work and considerations if proceeding. Further, six key areas were identified as critical for the CSC in moving forward in servitized offerings: communication and demonstration of service value, servitization offer and business case, managing of transformation, learning and feedback, internal alignment, and increased collaboration within the network. The study also concluded that the acceptance of new business models in this case is very much dependent on the regulatory requirements in the market which highly influence the possibilities in this field. Furthermore, the study showed that the main drivers for the CSC and ENCs can be divided into market drivers, financial drivers, and strategic drivers. Lastly, the study also concluded that both the CSC and the ENCs emphasized increased collaboration as an important factor going forward in the development of service offerings.
Keywords: servitization; product service systems; hybrid offerings; advanced services; differentiation strategy; drivers; energy sector; cable manufacturing industry